The Role of Audit Committee and Risk Monitoring Committee on Firm’s Hedging Practice - Zafira, Ananda Puteri; Hermawan, Ancella A. (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p10, 2023)
This study aims to analyze the role of audit committee and risk monitoring committee (RMC) on firm risk management measured by hedging. Firms with both committees will have better governance in monitoring risk. The population of this study is companies listed in IDX. This study uses samples of 104 non-financial companies. Using panel data regression, we find that the composition of audit committee members who have financial and/or accounting background have a significantly positive effect on hedging, meaning that an audit committee with such a higher composition will encourage firms to hedge more to reduce risk exposure. Meanwhile meetings and size of audit committee are insignificant. The presence of RMC has a negatively significant effect on firm hedging, meaning that the firm is more capable in identifying risk to determine the most appropriate way to mitigate risk, where not all risk can be mitigated by hedging. Keywords: Audit Committee; Risk Monitoring Committee; Hedging